ANALISIS PEMANFAATAN MEDIA CANVA DALAM MENGEMBANGKAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS V SEKOLAH DASAR - Sofyan, Salma Raihana; Iva Sarifah; Mahmud Yunus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze Canva media's use in developing fifth-grade elementary school students' critical thinking skills. Critical thinking skills are one of the important competencies in the Independent Curriculum, but many students still have not shown these abilities optimally in the learning process. This study uses a descriptive qualitative approach. Data were collected through observation, interviews, and documentation of the learning process that utilizes Canva media. The subjects of the study were fifth-grade students at SDI Al Azhar 2 in Jakarta City. The results of the study showed that Canva media was able to attract students' attention, make it easier to understand the material, and encourage students to be more active in expressing opinions and compiling arguments. Canva also provides a wide exploration space for students to express ideas visually and creatively. Based on these findings, Canva media is worthy of being used as an alternative learning medium that supports the development of critical thinking skills of elementary school students.